On the use of static GPS measurements to record the tidal response of a small antarctic ice shelf (hells Gate ice shelf-Victoria Land) - A. Bondesan; CAPRA, Alessandro; A. Gubellini; J. L. Tison (1994)
Recent developments of GPS (Global Positioning System) technology provide a new powerful tool to study ice shelfocean dynamical interactions. Here we present results from feasibility tests on the use of static GPS measurements to locate grounding zones and study their impact on the ice shelf mechanical response. The Hells Gate Ice Shelf has been chosen as a study case owing to its vicinity from Terra Nova Bay Station and to the peculiar problems it raises to glaciologists and geophysicists. Technical and analytical problems are discussed and 5 short time lapse records, in various places at the ice shelf surface, are interpreted. Most of the survey stations appear to react fully hydrostatically to the tidal forcing, even during a secondary maximum of only a few centimeters amplitude. The most upstream station 4, located in a strait between Vegetation Island and the Northern Foothills, shows departure from hydrostatic equilibrium in accordance with a scheme of bedrock valley sides effects. The GPS curve recorded suggests that the ice shelf might not always behave elastically in grounding zones as also testified by periods of intense microseismic actiity into the ice shelf during part of the day.